The Outcomes of Superior Cavopulmonary Connection Operation: a Single Center Experience - Al-Dairy,Alwaleed (2017)
Abstract Introduction: The superior cavopulmonary connection operation is one of the stages of the palliative surgical management for patients with functionally single ventricle. After surviving this stage, the patients are potential candidates for the final palliative procedure: the Fontan operation. Objectives: This study aimed to analyze the outcomes of superior cavopulmonary connection operations in our center and to identify factors affecting the survival and the progression to Fontan stage. Methods: The outcomes of 161 patients were retrospectively analyzed after undergoing superior cavopulmonary connection operation in our center between 2005 and 2015. Results: The early mortality rate was 2.5%. Five (3.1%) patients underwent takedown of the superior cavopulmonary connection. The rate of exclusion from the Fontan stage was 8.3%. Statistical analysis revealed that elevated mean pulmonary artery pressure preoperatively and the prior palliation with pulmonary artery banding were risk factors for both early mortality and takedown; however, the age, the morphology of the single ventricle and the type of operation were not considered risk factors. Conclusion: The superior cavopulmonary connection operation can be performed with low rate mortality and morbidity; however, the elevated mean pulmonary artery pressure preoperatively and the prior pulmonary artery banding are associated with poor outcomes.